Uma abordagem dialógica de A Hora da Estrela de Clarice Lispector - Melo, Robson Tavares de (2009)
This investigation has as proposal to observe the organization of the language inside of a romance, in other words, as the author conceives the language for the composition of his work. The romance is not just a literary manifestation; it is before everything a linguistic event, because the language is in the heart of its structure. To think the romance is to think in the language construction itself at a given style. The theoretical core of this work is the Russian linguist Mikhail Bakhtin s dialogic theory. According to Bakhtin (1997), every speech is social voice, that is permeated by other voices that are in the essence of the man's formation. In agreement with this thought, the monologist character of the speech is discarded. Like this, him (op. cit.) defends that the language, in its concrete totality, alive, in its real use, has property of being dialogic. These dialogic relations aren t restricted to the close field of the dialogue face to face, which is just a compositional form, of the multiple ones in that they happened. About the question of the romance, it is worth to point out that he occupies a prominence place in the works of Bakhtin, because to explain the dialogic phenomenon, Bakhtin made analysis in literary works. The romance is defined by him as: plurilinguistic, pluristylistic and social voice. The chosen work as object of study of this investigation is the Hour of the Star (1977), of the Ukrainian writer radicalized Brazilian, Clarice Lispector. This author belonging to the postmodernism (generation of 1945) composed this romance which besides uncoiling the romantic plot, makes reflections about the language and its manifestation. As for the story, Lispector approaches through a narrator-character the plot of a northeasterner from Alagoas that left her land, even without a defined destiny, and try the life in the big city. The romance is marked by disappointments and disillusions. Author's work mark, that blunt reflections about the human condition and the force of the language in the social relations, the ones that don't have this force are relegated to the social ostracism. The investigation in query will do through the romance selected linguistic reflections in the dialogic field. Themes as linguistic carnavalization, speech of other people, sign and ideology will occur in the analyses of this research. This research will raise contributions for the reflection and perception as for the dialogic construction presents in a literary work reaffirming as soon as beyond a literary event, the romance is a linguistic construction. With this research found that composed a novel in which oternes is the centerpierce of literary compositional structure.These contributions have as main objective to give support of linguistic valor to professors and students that have the language and literature as principal points of their researches